An analysis of smallholder farmer’s perceptions on climate change and changes in weather patterns compared to meteorological data in uMziwabantu, Ugu District, KwaZulu-Natal - Madakadze, Ignatious Casper (University of Pretoria, 2021)
Mini Dissertation (MA (Environment and Society))--University of Pretoria, 2021.